2022
DOI: 10.21203/rs.3.rs-1240394/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dexmedetomidine Alleviates Inflammatory Response and Oxidative Stress Injury of Vascular Smooth Muscle Cell via α2AR/PI3K/AKT Pathway in Intracranial Aneurysm

Abstract: Vascular smooth muscle cell (VSMC) phenotypic modulation regulates the initiation and progression of intracranial aneurysm (IA). Dexmedetomidine (DEX) is reported to play neuroprotective roles in patients with craniocerebral injury. Therefore, we investigate the biological functions of DEX and its mechanisms against IA formation and progression. Rat primary VSMCs were isolated from Sprague-Dawley rats. IA and STA tissue samples were obtained from patients with IA. Hydrogen peroxide (H2O2) was used to mimic IA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…On the other hand, Dex co-treatment elevated the BDNF expression and reversed the MTX-induced oxidative stress, as evidenced by the escalated SOD, and decreased MDA levels in the Dex co-treated group when compared to the MTX-treated rats. Similarly, previous studies have reported that Dex is able to alleviate oxidative stress injury in the vascular smooth muscle and lungs [54][55][56]. Together, our results reveal that Dex administration reduces the neurotoxic effect of MTX via upregulating BDNF expression and reducing oxidative stress in rats' hippocampus.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, Dex co-treatment elevated the BDNF expression and reversed the MTX-induced oxidative stress, as evidenced by the escalated SOD, and decreased MDA levels in the Dex co-treated group when compared to the MTX-treated rats. Similarly, previous studies have reported that Dex is able to alleviate oxidative stress injury in the vascular smooth muscle and lungs [54][55][56]. Together, our results reveal that Dex administration reduces the neurotoxic effect of MTX via upregulating BDNF expression and reducing oxidative stress in rats' hippocampus.…”
Section: Discussionsupporting
confidence: 88%